A numerical investigation into the effects of long-term wave-induced loads on the cross structure of a wave-piercing trimaran. Issue 1 (1st January 2017) - Askarian Khoob, Abolfath; Ketabdari, Mohammad Javad
Abstract: In the present study, the numerical analysis of long-term prediction of wave-induced loads on cross structure of a trimaran ship has been studied. The computation of these wave loads was performed by the use of MAESTRO-Wave, which is a linear sea-keeping analysis code. A global FEM model of the trimaran with symmetric and asymmetric side hull configurations was constructed using MAESTRO software. Then, the distribution and trend of the load at the junction of the cross deck and the main hull were derived. Results demonstrate that the 20-year long-term predictions are about 20% larger than the 1-year predictions for responses in combined sailing speeds. The study offers useful information about wave loads for balancing seakeeping performance with other design considerations in the conceptual design of a wave piercing trimaran.